ANALISIS KEKUATAN PEMBEBANAN RANGKA PADA PERANCANGAN MESIN PENCETAK PELET MENGGUNAKAN SIMULASI SOLIDWORKS - Galih Anjasmoro (UNIVERSITAS ISLAM MALANG, 2022)
Pellet machine is a tool that is usually used to print pellets for chicken feed in the form of tubes. In the analysis of the loading strength of the frame in the design of the pellet machine, an analysis of the selection of the right material is carried out to hold the components contained in the pellet machine. The material variables used in the analysis are: AISI 304, AISI 1020, and AISI 1045 and use L profile steel with a size of 40 mm × 40 mm, C channel steel with a size of 50 mm × 50 mm.This analysis uses the Solidworks 2018 software, from this analysis several materials are selected with a thickness of the L profile of 3 mm and the C channel 5 mm.The results of the simulation analysis on the maximum deflection pellet machine AISI 304 = 0.026 mm, AISI 1020 = 0.025 mm, and AISI 1045 = 0.024 mm. The results of the analysis of the maximum stress obtained values of AISI 304 = 3.821 N/mm2, AISI 1020 = 3.821 N/mm2, and AISI 1045 = 3.816 N/mm2. The results of the safety factor analysis obtained the value of AISI 304 = 54, AISI 1020 = 92, and AISI 1045 139.